Menumbuhkan Keterampilan Wirausaha Melalui Pelatihan di Kalangan Ibu-Ibu Hingga Anak-Anak Desa Ridogalih, Kec.Cibarusah, Kab. Bekasi - Retnowaty Silaban, Feronika; Syahra, Zahrisa Alifia; Ramadhani, Muthia Shabira; Noviyanti , Risma; Komalasari, Novi (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2025)
The implementation of this BSI Explore activity aims to contribute to growing entrepreneurial skills, as one of the efforts in order to develop life skills for residents of Ridogalih Village, one of the villages in Cibarusah District, Bekasi Regency, which has great potential in the development of micro businesses. However, the lack of entrepreneurial skills and knowledge becomes an obstacle for the community in developing their economic potential. Therefore, this activity intends to provide two training programs, namely making dish soap for mothers and making bracelets for children. The training methods provided include providing training facilities in the form of tools and materials, manufacturing demonstrations, and assistance. The results of these two programs show the improvement of participants' skills in their respective fields, as well as opening opportunities for mothers and children to develop creative businesses that can improve the family economy and Ridogalih Village.